Return of the tariffs: The interwar trade collapse revisited - Marc Christopher Adam (Freie Universität Berlin, School of Business & Economics, 2019)
Was the collapse of world trade between 1928 and 1937 caused by higher transport costs, increased protectionism or the collapse of the gold standard? Using recent advances in the estimation of gravity equations, I examine the partial and general equilibrium effects of bilateral distance, international borders, and the payment system on trade. My results suggest that had average tari and non-tari trade barriers remained at their 1928 level, total international trade would have been 64.6 % higher in 1937. Had the gold standard not collapsed in 1931 and had the British Empire not departed to establish its own currency and trade blocs, international trade would have been 3 % larger. Finally, had transport costs remained at their 1928 level, global trade would not have been significantly different nine years on. These results are supported by over 6,000 new hand-collected observations of ad-valorem ocean freight rates for cotton, which show an average increase of only 1.2 percentage points between 1928 and 1936. When expressed as an index, the movement of freight rates mirrors the evolution of the elasticity of trade to distance over the period.
urn:nbn:de:kobv:188-refubium-24959-1
Keywords: F10; F12; F13; F33; N70; 330; International trade; Gravity equation; Great Depression